Biomedicalization of death: a review - Flores-Pons, Gemma; Íñiguez-Rueda, Lupicinio (Anales de Psicología / Annals of Psychology, 2012)
Biomedicine has played an essential role in death's definition by stablishing it as an object of technoscientific knowledge as well as constituting and performing it through biomedical practices, its technical equipments and its spaces of action. In this article we draw a route for recent works involving principal issues of study around the biomedicalización of death as are (I) the good death, (II) being in and for death, (III) palliative care, (IV) death as a decision, (V) resuscitation practices, (VI) the technological death in the Intensive Care Units (ICU) and (VII) brain death. Furthermore, we do a fast approach to the works through the research perspectives and traditions that they are mobilizing. Death is presented as a controverted fact in the existing society and are multiple fields of medicine in which it is spread as such. It results unmistakeable that according to how death is defined, debates that accompany it will be defined and vice versa, according to which are the worries about death, will be delimited what it is, in what terms and through which practices it can be defined.